Implementation of Collaborative Learning Based on Sharing task Activi-ties on the Topic of Factors Afecting Reaction Rate - Sari, Wiwik Kartika; Drastisianti, Apriliana; Nada, Ella Izzatin (Universitas Sebelas Maret, 2020)
Learning of 21st century emphasizes the ability of students to find out from various sources, formulate problems, think analytically, and collaborate in solving problems. Collaboration will occur when classroom interactions between teacher and students can critically integrate topics, express, listen to multiple voices and points of view, and create effective learning relationships. The aims of this study was to analyze collaborative learning that occurs between students based on the sharing task activities that have been designed. This research was conducted on XI grade high school students. The data was taken from the topic of factors affecting reaction rate. The research method used is descriptive qualitative. The instruments used were didactic designs and student worksheets that have been declared valid by experts. The learning process is observed and recorded. Based on the results of observations and videos, student activities were analyzed which parts showed collaboration between students during the learning process using sharing tasks. Collaboration that occurs between students shows a quality learning process.